Business English : Burnett, M.J., Dollar, Alta - Burnett, M.J.; Dollar, Alta (Boston : Allyn and Bacon, 1979)
Learning tool for better use of English language in various business environments.
v. 1. Personal meetings. Disc 1. Unit 1. Formal meetings. Disc 2. Unit 2. Impromptu discussions. Disc 3. Unit 3. Monetary transactions -- v. 2. Contacts & correspondence. Disc 1. Unit 4. Telephine contacts. Disc 2. Unit 5. Appintments and activities. Disc 3. Unit 6. E-Mail, memos and letters -- v. 3. Career advancement. Disc 1. Unit 7. Resumés and interviews. Disc 2. Unit 8. Teamwork and problem solving. Disc 3. Unit 9. Assignment in U.S. or U.K.
System requirements: IBM PC Pentium 100 processor; Windows 98 or 95.
Keywords: English language -- Business English